Current Discussions on Employees and Organizations During the COVID-19 Pandemic: A Systematic Literature Review - Mun, Soyeon; Moon, Yoosun; Kim, Hayeseul; Kim, Namhee (Frontiers in Psychology, 2022)
New concerns have emerged during the COVID-19 pandemic that greatly impact employees and many other aspects in organizations. We have highlighted the major organizational themes during COVID-19 and classified the relevant research findings based on 45 recent articles. Main themes identified include (1) Work setting, (2) Perceptions of COVID-19, (3) Employee well-being, (4) Organizational strategies, and (5) Influences on career behaviors. Employees have faced challenges due to work conditions that have shifted from traditional commuting to telework. Employees have also become aware of the negative current situation, so their overall well-being has been threatened. In response, organizations have strived to promote positive psychological capital for employees as they attempt to cope with this crisis. Organizations have tried to maintain and manage both their employees and their business. People tended to adjust their career-related behaviors based on how they perceived their own well-being and organizational strategies.